The formation of the superior and jugular ganglia: insights into the generation of sensory neurons by the neural crest. - Thompson, H; Blentic, A; Watson, S; Begbie, J; Graham, A (2010)
The superior and jugular ganglia (S/JG) are the proximal ganglia of the IXth and Xth cranial nerves and the sensory neurons of these ganglia are neural crest derived. However, it has been unclear the extent to which their differentiation resembles that of the Dorsal Root Ganglia (DRGs). In the DRGs, neural crest cells undergo neuronal differentiation just after the onset of migration and there is evidence suggesting that these cells are pre-specified towards a sensory fate. We have analysed sensory neuronal differentiation in the S/JG. We show, in keeping with previous studies, that neuronal differentiation initiates long after the cessation of neural crest migration. We also find no evidence for the existence of migratory neural crest cells pre-specified towards a sensory phenotype prior to ganglion formation. Rather our results suggest that sensory neuronal differentiation in the S/JG is the result of localised spatiotemporal cues.